Practical agricultural communication: Incorporating scientific and indigenous knowledge for climate mitigation - Sereenonchai, Sukanya; Arunrat, Noppol (Kasetsart Journal of Social Sciences, 2019)
Agricultural communication to mitigate climate change enables information dissemination of both scientific knowledge (SCK) and indigenous knowledge (IDK) for practical farming. This research analyzed knowledge utilization and conducted community-based participatory communication to propose a practical agricultural communication framework for climate mitigation. Based on a qualitative method of data collection in Phichit province, the key findings showed that SCK and IDK can be mutually utilized to enhance the good relationship among the people and for the people with nature. The participatory communication processes consisted of planning, interventions, and monitoring and empowerment. The successful farmers employing the farming practices of not burning rice straw, rice straw composting, and alternative wetting and drying technique were the main senders. The messages were related to their farming practices focusing on a practical and understandable message and graphic explanations. Vinyl was selected as a communication material for signage in the most noticeable areas in their communities. This research highlights that participatory communication with group dynamics and communication promotion mechanisms at both local and national levels should be enhanced.